Influence of Consumer Perception and Packaging Design on the Increase of Consumer Satisfaction with Packaged Drinking Water - Fernando, Rio; Asrol, Muhammad (Jurnal Ilmiah Global Education, 2025)
The Indonesian Bottled Drinking Water (AMDK) industry faces complex and multidimensional challenges, especially those related to consumer satisfaction and environmental sustainability. One of the main issues highlighted is consumer dissatisfaction with the current AMDK packaging, which is often considered impractical, environmentally unfriendly, and raises concerns about the safety and cleanliness of the water content. These concerns significantly influence consumer preferences and purchasing behavior in a highly competitive market. The main objective of this study is to identify the influence of consumer perceptions of the quality, safety, and added value of AMDK products on overall consumption satisfaction. The research method consists of several stages, including problem identification, literature study focusing on the application of the Quality Function Deployment (QFD) method in developing Bottled Drinking Water products, formulation of survey questions regarding factors that influence purchasing decisions, and identification of critical attributes through QFD analysis. The research findings show a strong positive response from respondents at the questionnaire validation stage. Consumers highly value aspects such as innovative product design, use of high-quality and environmentally friendly materials, appropriate capacity, increased bottle thickness, and the potential for large-scale production of the product. These results suggest that integrating consumer input into the product development process can significantly improve satisfaction and market acceptance.